DIGITAL TECHNOLOGIES AND CIVIC ACTIVISM: CURRENT SOCIOLOGICAL APPROACHES TO THE STUDY OF THE PROBLEM - Minzaripov, Riyaz; Eflova, Maria; Maximova, Olga; Ozerova, Karina (Revista Inclusiones, 2020)
The purpose of the present study is to describe current research prospects in the field of sociological analysis of civic activism in the context of digitalization and the spread of digital technologies. It is concluded that the discourse of sociological research on digitalization is changing. Currently, digital technologies serve not only as a factor in the growth of citizens' freedom, but also become a means to increase social control by the state, as well as lead to the dispersion of social activity, and reduce its transformative power.